ANALISIS KEPUASAN PELANGGAN UNTUK MENINGKATKAN KUALITAS PELAYANAN ADMISI DAN PROMOSI UNIVERSITAS BAKRIE - Aries Wiwit Handayani (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. Approach to discover customer expectations is needed to improve thecompetitiveness of the university. This study aims to determine the characteristicsof services which do not satisfy customer expectations and provide advice onimproving service quality Admission and Promotion Bureau Universitas Bakrie.This research used ServQual method to measure customer expectations andperceptions. Information was gathered by a questionnaire with Likert scale.Proceed with observation and interviews with Universitas Bakrie management toanalyze of the Quality Function Deployment (QFD) by the House of Quality(HOQ) first stage. The results show that 17 indicators in five dimensionsServQual have greater customer expectations of perception. Dimensions tangibleson the first rank of customer dissatisfaction. Generaly, the service characteristicsin Admission and Promotion Bureau did not meet customer expectations includeunoptimal the use of communications technology, registration facilities wereinadequate, and service staff Admission and Promotion Bureu did not maximalyet.Then followed sequentially reliability, responsiveness, assurance, andempathy. The main recommendation in this research is the provision of adequatecommunication tools to cut the distance between the consumer and Admissionand Promotion Bureau and internal member Admission and Promotion Bureau.The findings in this research may help management to enhance service quality toincrease customer satisfaction.Keywords: quality, service,admission and promotion, ServQual, QFD, HOQ